The Role of Diabetes and Hyperglycemia on COVID-19 Infection Course—A Narrative Review - Tzeravini, Evangelia; Stratigakos, Eleftherios; Siafarikas, Chris; Tentolouris, Anastasios; Tentolouris, Nikolaos (Frontiers in Clinical Diabetes and Healthcare, 2022)
It was previously reported that subjects with diabetes mellitus (DM) are more vulnerable to several bacterial or viral infections. In the era of coronavirus disease 2019 (COVID-19) pandemic, it is reasonable to wonder whether DM is a risk factor for COVID-19 infection, too. It is not yet clear whether DM increases the risk for contracting COVID-19 infection or not. However, patients with DM when infected are more likely to develop severe or even fatal COVID-19 disease course than patients without DM. Certain characteristics of DM patients may also deteriorate prognosis. On the other hand, hyperglycemia per se is related to unfavorable outcomes, and the risk may be higher for COVID-19 subjects without pre-existing DM. In addition, individuals with DM may experience prolonged symptoms, need readmission, or develop complications such as mucormycosis long after recovery from COVID-19; close follow-up is hence necessary in some selected cases. We here present a narrative review of the literature in order to set light into the relationship between COVID-19 infection and DM/hyperglycemia.